Pertumbuhan Berbagai Varietas Bawang Putih (Allium Sativum L.) dengan Media Tanam pada Dataran Rendah Secara Terapung - Nurlaila Nurlaila; Benyamin Lakitan; Fitra Gustiar (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Garlic (Allium sativum L.) is one of the horticultural commodities grown using a floating agriculture system. This study aims to determine the effect of variety and growing media on the growth and yield of garlic (Allium sativum L.) in a floating cultivation system. The research was conducted in Pelabuhan Dalam Village, Pemulutan District, Ogan Ilir Regency, South Sumatra. The method used is a Factorial Randomized Block Design consisting of two treatment factors. The first factor is the variety, consisting of K1 (Tawangmangu), K2 (Lumbu putih), K3 (Lumbuh hijau). The second factor is the growing medium, consisting of M1 = Soil: Manure: Burned Rice Husk (2:1:1), M2 = Soil: Manure: Cocopeat (2:1:1). The research results show that the variety has a significant effect on most growth and yield parameters, while the growing media does not have a significant effect on all parameters. Variety K2 (Lumbu Putih) provided the best growth and yield, as indicated by the fresh tuber weight, dry tuber weight, fresh leaf weight, dry leaf weight, and number of tubers. The interaction between variety and growing media did not show a significant effect on all parameters. Nevertheless, the combination of K2M1 (Lumbu Putih + burned rice husk) tends to produce the best growth and yield with fresh tuber weight, dry tuber weight, and number of tubers. Based on the research results, the Lumbu Putih (K2) variety with burned rice husk (M1) as the growing medium has the potential to be developed in a floating cultivation system.